Religious Law vs. Secular Law: The Struggle for Justice in Indonesia’s Legal System (Indonesian Theological Justice Review, 2025)
Indonesia’s legal system, a complex blend of religious and secular laws, often creates tensions between religious justice and civil justice. This paper critically examines the intersection of religious laws—such as Islamic Sharia law—and the country’s secular legal framework, and the implications this has for justice. The study focuses on areas where these two systems overlap or conflict, including family law, inheritance, and criminal justice. Islamic law, which influences a significant portion of the population, offers unique perspectives on justice, but its integration with Indonesia’s national legal framework has sparked debates on legal pluralism and human rights. The paper explores key cases where religious and secular laws have clashed, considering how religious laws are applied to different segments of society, including religious minorities. The research also examines how the secular state navigates these tensions, balancing national legal standards with religious principles. The paper assesses how these tensions affect access to justice for marginalized groups, particularly women and religious minorities, and suggests possible legal reforms to ensure that both religious and secular laws can coexist to protect human rights and promote justice.